2022
DOI: 10.3389/fpsyg.2022.1053512
|View full text |Cite
|
Sign up to set email alerts
|

The crisis of international education students and responsive service in and after COVID-19 pandemic

Abstract: ) The crisis of international education students and responsive service in and after COVIDpandemic. Front. Psychol. : . doi: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Considering the increase in international students’ mobility—e.g., 6.1 million students were enrolled outside their home country in 2019 [ 17 ]—proactive initiatives could be taken to prevent and promote their mental health, even beyond the COVID-19 pandemic[ 43 ]. In Germany, a sense of belonging has been pointed out as beneficial for international students’ adaptation and has been related to better well-being, higher study satisfaction, and lower drop-out intention [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the increase in international students’ mobility—e.g., 6.1 million students were enrolled outside their home country in 2019 [ 17 ]—proactive initiatives could be taken to prevent and promote their mental health, even beyond the COVID-19 pandemic[ 43 ]. In Germany, a sense of belonging has been pointed out as beneficial for international students’ adaptation and has been related to better well-being, higher study satisfaction, and lower drop-out intention [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted in China indicated hopelessness, uncertainty, worry, lack of interest and focus, lack of support, financial difficulties, social pressure, sleep disorders, and increased smoking among international students [28]. Therefore, visa and financial issues, language skills, acculturation problems, poor social support systems, cultural and social adjustment, academic adaptation, homesickness, and lack of knowledge about the healthcare system are some examples of the challenges faced by international students in particular [17,[43][44][45][46].…”
Section: Plos Onementioning
confidence: 99%
“…The perceptions of international students toward the COVID-19 pandemic have been surveyed in many countries [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Despite the discrepancy in the government policy and disease burden across the countries in these studies, all the findings indicated that international students confronted various aspects of mental problems [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%